The influence of psycho – exercise rehabilitation on some physiological variable for arteries patients after Cardiac re-open for the male (50-55) years old - bedulsattar, Basil (Journal of Physical Education, 2012)
The development technology in present life make a negative influence on human hygiene especial on cardiovascular and respiratory system, diagnosis by International Association for Health (IAH).The problem of the study lies in the limited of the rehabilitation programs within hospitals and clinics.The aim of the study in to identify the effect of the rehabilitation program on some physiological variables of heart activity.The hypothesis of the study confirm a statistical differences between pre and post test for the benefit of rehabilitation program.The study has been done on six subjects who suffer from weak arteries disease after re-open cardiac.The researcher used experimental design for one month, three times a week, with (20-30) minutes for each training day.The study has concluded that the use of respiratory exercise was positive effect to improve cardiac function.The researcher recommended that the respiratory exercise is highly effect to improve heart hygiene and activity.